The circus as idolatrous temple in Tertullian ('Spect.', 8.4; 13.4) - Baptista, Natan Henrique Taveira (Romanitas - Revista de Estudos Grecolatinos, 2015)
This paper aims to debate the rejection of the circus space, as well as the manifestations of entertainment practiced within it, and its meaning for the Paleochristian neophyte’s life, based on the Tertullian’s scriptures – in particular ‘Of public shows’ (De Spectaculis). In order to justify his statements, the North African author metaphorically associated both venues and monuments in circus and pagan temples, which led his argumentation to identify attending chariot races as an idolatrous practice. We argue that Tertullian’s aims with such sanctions were to control the sociability of Carthage’s proto-orthodox community members, as to mark the identity of this group in contrast with the identities of pagans. In order to answer our questions, we have analyzed our primary archives through a critical textual examination of the Content Analysis, following the method proposed by Laurence Bardin.
Keywords: Carthage; Paleochristianism; Tertullian; Circus; Ludi Circenses